Effectiveness of the Problem Based Learning Approach in Improving Skills in Writing Exposition Text - Siti Aisyah Sumartini (Alinea: Jurnal Bahasa, Sastra, dan Pengajaran, 2019)
This article will describe the effectiveness of the problem based learning approach in improving exposition text writing skills. The method used in the study was an experiment with the design Randomize Pretest-Posttest Control Group with test techniques and questionnaires. The result shows that the average value of the experimental class pretetst 59.97, and posttest 85.76, while the average value of pretest in the control class 58.91, and posttest 67.53. To see the increase in each class, an N-gain test is performed. Based on the test results it was found that in the experimental class there were 18 students who had high writing skills, 12 students with moderate writing skills, and 4 students who had low writing skills, while in the control class there were 3 students who had high writing skills, 16 students with abilities moderate writing, and 15 students who have low writing skills. Based on this, it can be concluded that the Problem Based Learning approach is very effectively used in learning activities in exposition text writing. Keywords: Problem Based Learning, writing,  exposition text